2007
DOI: 10.1083/jcb.200612116
|View full text |Cite
|
Sign up to set email alerts
|

12R-lipoxygenase deficiency disrupts epidermal barrier function

Abstract: 12R-lipoxygenase (12R-LOX) and the epidermal LOX-3 (eLOX-3) constitute a novel LOX pathway involved in terminal differentiation in skin. This view is supported by recent studies showing that inactivating mutations in 12R-LOX and eLOX-3 are linked to the development of autosomal recessive congenital ichthyosis. We show that 12R-LOX deficiency in mice results in a severe impairment of skin barrier function. Loss of barrier function occurs without alterations in proliferation and stratified organization of the ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
172
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 173 publications
(194 citation statements)
references
References 51 publications
13
172
0
1
Order By: Relevance
“…The antibody raised against rat 12S-LOX (HXA 3 synthase) recognized also human epidermal 12S-LOX (HXA 3 synthase). As mutated eLOX3 is still expressed at the protein level in cells [7,8], these findings suggest to us that the patient in the case study has a different ichthyosis form than that reported for NCIE patients, who showed deficiency of 12R-LOX or eLOX3 due to gene mutations [5][6][7].…”
Section: Gc-ms Analysissupporting
confidence: 52%
See 1 more Smart Citation
“…The antibody raised against rat 12S-LOX (HXA 3 synthase) recognized also human epidermal 12S-LOX (HXA 3 synthase). As mutated eLOX3 is still expressed at the protein level in cells [7,8], these findings suggest to us that the patient in the case study has a different ichthyosis form than that reported for NCIE patients, who showed deficiency of 12R-LOX or eLOX3 due to gene mutations [5][6][7].…”
Section: Gc-ms Analysissupporting
confidence: 52%
“…HXALI patient does not exhibit any of these symptoms, obviously because of the overexpression of 12R-LOX. Furthermore, it has been reported that in mice deficient of 12R-LOX processing of profilaggerin to filaggrin, which aggregates keratin filaments to form macrofibrils in cornified cells of the stratum corneum, is impaired, resulting in decreased integrity of the cornified envelop [8]. Reduced proteolytic processing of filaggrin in humans has been shown to cause ichthyosis vulgaris [18].…”
Section: Discussionmentioning
confidence: 99%
“…In murine skin wounds, there are other lipoxygenases, including epidermis-type LOX3, 12R-LOX, and 8-LOX as well as 5-LOX from recruited leukocytes (26,30,31,50,(53)(54)(55)(56)(57)(58)(59). However, LOX3, 12R-LOX, 8-LOX, or 5-LOX is unlikely to catalyze DHA 14S-hydroxygenation in skin wounds based on the study conducted by other scientists (52) and ourselves.…”
Section: Discussionmentioning
confidence: 89%
“…157,158 In recent years, it has become evident that this most critical SC functionethe permeability barriereis impaired in most ichthyosis forms. 11,60,[159][160][161][162][163][164] Several murine knockout models for ichthyosis [Spink5 (e/e), Tgm1 (e/e), Abca12 (e/e) mice, [165][166][167] Alox12b (e/e), 168 Cldn1(e/e) 169 ] have demonstrated neonatal lethality as a result of dehydration, underscoring the critical role of these genes in permeability barrier competence. Mutations that either alter the lipid composition of the SC membranesedisorders of lipid metabolismeor affect the function of the corneocyte structural proteinsedisorders of keratinocyte proteinseresult in increased water movement through the intercellular pathway.…”
Section: Concept Of the Impaired Permeability Barrier And Homeostaticmentioning
confidence: 99%